2020
DOI: 10.21608/ejnf.2020.148152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phytase Enzyme and Citric Acid on Productive Performance, Nutrient Retention and Tibia Bone of Broiler Chicks Fed Low Available Phosphorus Diet

Abstract: he study investigate the effect of feeding low available phosphorus (AP) diet supplemented with three levels of microbial phytase (MP) and /or three levels of citric acid (CA) on broiler performance, tibia bone and nutrient retention. Four hundred day-old Ross broiler chicks were randomly allocated into ten treated groups, with four replicates of 10 birds each. The chicks were fed ten different diets as normal phosphorus 0.45% AP (positive control, PC) and nine groups with phosphorus deficient diets 0.25% AP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…Notably, the addition of CA, either with fungal or bacterial phytase, did not show any significant beneficial or detrimental impact on growth performance, serum mineral profiles, bone quality, or nutrient retention. The positive effect of CA combined with the phytase enzyme on broiler performance was reported by several researchers [ 5 , 7 ]; whereas some also observed negative or no effects on overall performances [ 26 , 38 ]. Optimum levels of these two compounds may represent a possible solution to improve P utilization and overall performance without any additive or synergistic effects in broilers.…”
Section: Discussionmentioning
confidence: 78%
“…Notably, the addition of CA, either with fungal or bacterial phytase, did not show any significant beneficial or detrimental impact on growth performance, serum mineral profiles, bone quality, or nutrient retention. The positive effect of CA combined with the phytase enzyme on broiler performance was reported by several researchers [ 5 , 7 ]; whereas some also observed negative or no effects on overall performances [ 26 , 38 ]. Optimum levels of these two compounds may represent a possible solution to improve P utilization and overall performance without any additive or synergistic effects in broilers.…”
Section: Discussionmentioning
confidence: 78%
“…Similar results were observed by Hao et al (2017) [25] who used two doses of phytase (300 and 500 IU) in broiler diet. Also, Soliman and Al-Youssef (2020) [44] found that the supplementation of microbial phytase (500 FTU/Kg) with 1 or 2% citric acid into the control diet (P≤0.05) improved (BWG) of chicks. As well as, Khan et al (2019) [34] who observed significantly higher differences (P<0.05) in FCR, live body weight in experimental groups treated with phytase enzyme compared to the control group.…”
Section: Growth Performancementioning
confidence: 99%
“…While, feed intake was minimum in broiler fed basal diet provided ~ 375 ~ with phytase 0.075 g/Kg. Feed intake and feed conversion ratio significantly increased due to adding 1% citric acid and microbial phytase levels into control diet, (Soliman and Al-Youssef 2020) [44] . Supplementation of NSP enzymes, synbiotics and phytase alone or in combination had a significant effect on feed intake, (Narasimha et al 2013) [45] .…”
Section: Feed Intake and Fed Conversionmentioning
confidence: 99%